PELAKSANAAN PELAYANAN PUBLIK YANG BERKUALITAS - Permatasari, Arini (Decision, 2020)
A government efforts to create good service or maximal to society not yet thoroughly reached because still complaint quantity and society criticism towards performance apparatus bureaucracy never decreased. Various wisdom stills to received as symbolic by government, because in carry out law and regulation not yet thoroughly on the basis of for public service enhanced, but only carry out higher instruction. The mentioned is watched from inwrought service unit formation or pattern service pattern one roof at region not yet achieve target, because inwrought service unit that is formed not yet ambulatory well. Keywords : good government, service